ANALISIS PENGALAMAN MAHASISWA DALAM MENGEMBANGKAN KEGIATAN BISNIS CAFÉ DI HOTEL KAMPUS POLITEKNIK BANYUWANGI - Reni Nur Jannah; Diana Martalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify the experiences of Hospitality Management students in developing a campus café business at Banyuwangi Polytechnic as part of their fourth semester project activities. The focus of this study is to identify project activities, obstacles and challenges, and strategies implemented by students by utilizing management principles during the production of goods and services, café management, and human resource management. The research method used is a qualitative approach, with data collection through observation, interviews and documentation. The collected data were analyzed using manual coding and a SWOT analysis approach. The results of the study indicate that managing this real project provides valuable experience for students in developing practical and soft skills, the main obstacles and challenges are limited space facilities and standard restaurant utensils, limited preparation, and equal distribution of student competencies. To overcome these obstacles, students implemented several strategies, namely conducting thorough planning for both the room and restaurant utensil facilities, thorough human resource planning and intensive mentoring by the teaching team. Recommendations from this study are to strengthen the curriculum, provide supporting facilities and increase the role of the teaching team. So, with proper and more mature planning, students are expected to be able to manage the cafe business project more smoothly and keep the cafe business project going for the next batch of hospitality management students as well as become good role models for other study programs.